Strategic PR Guidelines for Marketing Planning to Ensure the Sustainable Development of Socio-Economic Systems - Iryna Martusenko; Inna Boychuk; Nadiia Baluk; Lesia Sai; Tetiana Fursa (International Journal of Sustainable Development and Planning, 2023)
The main purpose of the article is to determine the strategic public relations (PR) guidelines for marketing planning the sustainable development of the socio-economic system in the region. The research methodology provides for the use of modern methods of taxonomic analysis, linear trend and multivariate correlation and regression analysis. As a result, an integral indicator of sustainable development of the agricultural sector of a particular region was determined. Comparatively and estimated the level in the dynamics of the last few years. Modeling of indicators of sustainable development was carried out in order to determine the strategic orientation for planning for this region. The recommended strategic PR-landmark for enterprises of the region has been determined for the purpose of further sustainable development. The study is limited by not taking into account all possible indicators and focusing only on a specific area of activity and region.
Стратегічні рекомендації з PR для маркетингового планування з метою забезпечення сталого розвитку соціально-економічних систем
Keywords: sustainable development; planning; region; strategic guidelines; socio-economic systems; systems